Enhancing Student Learning Outcomes through the Integration of Technology in Pedagogy (Eurasian Scientific Herald, 2023)
This scientific article aims to explore the use of technology in pedagogy and its impact on student learning outcomes. The rapid advancements in technology have revolutionized various sectors, including education. As traditional teaching methods are gradually integrating with digital tools and resources, it is essential to examine the effectiveness of this innovative module on student learning outcomes. This article presents a comprehensive review of relevant literature, highlighting the potential benefits and challenges associated with the use of technology in pedagogy. Moreover, it discusses various examples of successful implementation and highlights key strategies to maximize the positive impact of technology on student learning outcomes.